PENGEMBANGAN MODEL PEMBELAJARAN BETTER TEACHING AND LEARNING BERKARAKTER UNTUK MEMBEKALI KOMPETENSI PEDAGOGI MAHASISWA CALON GURU - Rusilowati, Ani; Hartono, Hartono; Supriyadi, Supriyadi (Universitas Negeri Semarang, 2012)
Aim of research is: (1) developing model study of Better Teaching And Learning with character (BTL-K) able to grow character, improving enthusiasm, activity, and result learn student, determining is valid, effectiveness and is practical of model study of developed BTL-K. This research represent research of development (R&D). Research executed in three phase, that is: (1) eksplorasi by teoretis and expert reviu to model of BTL-K. (2) empirical Test, for memvalidasi empirically model of BTL-K. (3) Phase implementation, to know effectiveness and is practical of model of BTL-K. Result of research indicate that model study of BTL-K the developed is to integrate character items into items of IPA (Physics), and presented at step of connection at network do ICARE step. This Model is expressed valid by validator and supported with result of validasi by empirik through field ujicoba. This model have also been tested by its effectiveness in grow character and improve enthusiasm, activity, and result learn cognately of student. Practical of applying of model of BTL-K this have also been tested to through observation to ability of teacher in learning in class, response learn to amenity of teacher in using model, and response keberterimaan of student to study model applied by teacher. End result indicate that model study of BTL-K the developed have fulfilled valid criterion, effectiveness, and is practical.